THE SOCIO-ECONOMIC GEOGRAPHICAL ANALYSIS OF THE KOTAYK PROVINCE RURAL AREAS (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Socio-economic geographic analysis of the Kotayk Province rural areas has been done in the article. It have been discussed the issues regarding to the province rural population and settlements forming, dynamics (1831–2015) and the modern situation. A special significance has been given to the changes in the rural resettlement structure of the province by the settlements population size, the distribution of population and settlements above sea level, as well as by the production specialization and socio-economic development problems of the rural settlements.
Keywords: Kotayk province; rural areas; dynamics of population and settlements; agricultural holdings specialization; development problems